Predictors of Physics Learning Outcomes: The Role of Prior Knowledge and Growth Mindset - Nur Arviyanto Himawan; Murtono Murtono; Zul Hidayatullah (Department of Physics Education, Universitas Mataram, 2026)
Growth mindset plays an important role in facilitating students' understanding of physics concepts. This study aimed to examine the effects of prior knowledge and growth mindset on students’ physics learning outcomes. A quantitative approach with a correlational research design was employed. The sample consisted of 36 students from the Physics Education Study Program at UIN Sunan Kalijaga who were enrolled in the Fundamental Physics course, selected using a saturated sampling technique. Data were collected using a growth mindset questionnaire, a prior test (pretest), and a physics learning outcomes test (posttest). The research instruments were validated and tested for reliability before use. Data were analyzed using descriptive and inferential statistics, including prerequisite tests, multiple linear regression, and Pearson correlation analysis. The results showed that prior knowledge and growth mindset jointly had a significant effect on physics learning outcomes, with an R value of 0.775 and an R² value of 0.600, indicating that the two variables explained 60% of the variance in learning outcomes. The ANOVA results confirmed that the regression model was statistically significant (F = 24.787, p < 0.001). Partially, prior knowledge had a positive and significant effect on physics learning outcomes (β = 0.689, p < 0.001), whereas growth mindset had a negative but non-significant effect (β = –0.414, p = 0.295). These findings indicate that prior knowledge is the dominant factor influencing students’ physics learning outcomes, whereas growth mindset serves as a complementary supporting factor. Therefore, instructional design should emphasize diagnostic assessment and the reinforcement of prerequisite knowledge before introducing new concepts. In addition, students’ growth mindset should continue to be fostered to encourage reflective learning and strengthen their confidence in overcoming academic challenges.